The prerequisites for the railways construction on the territory of Transcaucasia in the second half of the XIX th- beginning of the XX th century - Hurinchuk, S. V. (History of science and technology, 2018)
The article analyzes and summarizes the prerequisites for the railways construction on the territory of Transcaucasia in the second half of the XIX-beginning of the XX century. In a convinc-ing manner the author proves that the Caucasus with its diverse, inexhaustible mineral re-sourceswas rightly considered one of the richest parts of the globe.Drawing on the experience and achievements of national science and technology, the author of the article has grounds to assert that the railway transport has always been and still is the most important branch of the national economy,the lifeblood of the Russian economy in general and in particular of the Caucasus.It was found that the construction of the Transcaucasian railway had been caused by a number of strate-gic, political and economic considerations and circumstances.It was proved that at the beginning of the XXth century the Caucasus railway network had eliminated the administrative and economic isolation of some regions in the Caucasus.The natural history of its development strengthened so-cial and territorial division of labor, led to an active economic and cultural rapprochement of peo-ples of Transcaucasia and Russia.